Contextualising Indonesia-Japan Economic Partnership Agreement (IJEPA) within Strategic Partnership Framework: A Prelimanary Assesment - Zulhajnie Wildayanti (Kajian Asia Pasifik, 2020)
Abstract This article explains Indonesia’s rationale to prolong its cooperation with Japan under Indonesia-Japan Economic Partnership Agreement (IJEPA). This article utilises Wilkin’s Strategic Partnership framework to analyse the phenomenon. Under the aforementioned trade framework, Indonesia is still at disadvantageous position due to non-tariff barriers that is imposed by Japan. This article argues that Indonesia’s decision to prolong the agreement is because Japan – Indonesia economic partnership is intertwined with both parties security and ideological partnership.